Mechanisms of Public-Private Partnership - Karimov Akramjon Ikromjon ugli; Turayev Anvar Shokirovich (Research Parks Publishers, 2021)
In the article, authors allocate and describe a number of aspects of the mechanism of functioning of public-private partnership. They are named as organizational and legal, financial and investment, technical and organizational, regional.